ENERGY RELATIONS BETWEEN CHINA AND AZERBAIJAN: BETWEEN PRAGMATIC COOPERATION AND STRATEGIC PARTNERSHIP - Nikolic, Danijela; Rašković Talović, Violeta; Stojadinović, Miša (The Policy of National Security, 2025)
This paper analyses the contemporary relations between the People’s Republic of China and the Republic of Azerbaijan, focusing on the energy dimension of their cooperation and the impact of these relations on regional and broader energy security. In the context of China’s growing involvement in the South Caucasus and Azerbaijan’s strategic positioning as an essential transit and export energy hub, the paper seeks to address the key question of whether the relationship between Baku and Beijing represents a sustainable partnership based on complementary strategic interests or a limited, pragmatic cooperation driven by current economic and geopolitical circumstances. Special attention is given to the analysis of energy projects in which both states are directly or indirectly involved such as oil and gas pipelines as well as infrastructure initiatives like the Baku–Tbilisi–Kars railway, which connects China’s Belt and Road Initiative with Europe through Azerbaijani territory. Methodologically, the paper relies on a qualitative analysis of official bilateral documents, relevant scholarly and analytical literature, official government and institutional statements, reports from international energy organisations, and key infrastructural and energy project case studies. The theoretical framework is based on energy security, geoeconomics, and realpolitik, focusing on modelling energy relations as instruments of foreign policy influence. The paper also considers global geopolitical shifts, including the consequences of the conflict in Ukraine, changes in European energy strategy, and China’s position within the emerging multipolar order. The research contribution of this paper lies in its systematic assessment of the level of interdependence between China and Azerbaijan in the energy sector, as well as in evaluating the potential long-term stability of this relationship from the perspectives of regional security, economics, and politics.
Keywords: Azerbaijan; China; energy security; Belt and Road; geopolitics; energy; South Caucausus; infrastructure